Positive pedagogical practices, extracurricular involvement, community & school citizenship, and acquisition of 21st century skills among secondary students from Indonesia, Kyrgyzstan and Tanzania - Abdallah, Ssekamanya Siraje; Syed Mahmood, Syarifah Rohaniah (NAMA Foundation, 2024)
This research examines the role of positive pedagogical practices, extracurricular involvement, and community and school citizenship on the acquisition of the 21st century skills of Skill development, cognitive engagement and reflective learning. Data were collected from a sample of 864 secondary school students from the total of 63 schools from the three countries, namely, Indonesia, Kyrgyzstan, and Tanzania where the NAMA Foundation is operating the school improvement programs. This study is a small portion of the large-scale dataset evaluating the effectiveness of the NAMA interventions in the respective countries. Data were collected using an instrument that was designed and standardized for data collection across all schools in the project. Results were analyzed using the Smart PLS program, version 4, first, to determine the validity and reliability of the instruments and second to test the hypotheses of the study. An attempt was made to find out if the hypothesized model fits the data and secondly if there are any differences among students from Indonesia, Kyrgyzstan, and Tanzania on the measured constructs. The findings underscore a significant relationship between extracurricular involvement, community & school citizenship, and the development of 21st-century skills, mediated by positive pedagogical practices. Notably, no significant differences were observed among the participating countries, suggesting the potential universal applicability of these relationships across diverse cultural and geographical contexts. This research contributes to the discourse on effective educational practices, highlighting the importance of holistic approaches that encompass extracurricular engagement and community participation, facilitated by innovative teaching strategies. The insights gleaned underscore the critical role of contextually relevant pedagogies in equipping Muslim youth with the necessary competencies for success in the contemporary global landscape. The findings contribute to highlighting the significance of the interventions carried out by NAMA Foundation and similar efforts around the world.